Impact of Lockdown 1.0-4.0 on spread of COVID-19 Pandemic in India - Ranjan, Alok; Ayub, Arshad; Kumar, Abhishek; Pandey, Sanjay; Kumar, Pragya; Agarwal, Neeraj (Indian Journal of Community Health, 2020)
Novel Coronavirus Outbreak (COVID-19) was declared as a pandemic on 11th March 2020 by World Health Organization (WHO). This was a call for immediate action to be taken on by all countries in terms of stepping up treatment, detection, and reduction of transmission. A total of 26472012 confirmed cases with over 873229 deaths were reported as on 4th September 2020 worldwide. (1) Government of India, initiated various Non-Pharmaceutical Intervention (NPI) to break the chain of transmission and prevent the spread of COVID-19, which included social distancing, and restricted public mobility like lockdown. The largest COVID-19 national lockdown in India started on 25th march 2020. Still, India’s population of 1·3 billion across diverse states, health inequalities, widening economic and social disparities, and distinct cultural values present unique challenges.(2) Meanwhile nationwide lockdown was extended till 31st may 2020 by Ministry of Home Affairs, Government of India (Lockdown 4.0).(3) This lockdown strategy adopted by the country to curtail the impact and flatten/delay the peak of the COVID-19 pandemic, and it’s quantification may aid to plan future intervention strategies